Indirect determination of FMDV 146S component concentration in non-inactivated suspension by comparison of graphs of the second derivative for real-time RT-PCR curves - M. I. Doronin; D. V. Mikhalishin; V. A. Starikov; D. A. Lozovoy; A. V. Borisov (Ветеринария сегодня)
During reproduction in biological systems, FMD virus forms four variants of components, three of which do not include RNA of the virus. In the process of industrial production of FMD vaccines, special attention is paid to the number of whole virions, which have the most important biological properties of FMD virus and are the main components that determine the immunogenicity of vaccine preparations. Raw materials for vaccines at various stages of the technological process are tested for concentration of FMDV 146S component. The traditional method of determination is quantitative complement fixation test. In recent years, real-time RT-PCR has been used for indirect determination of FMDV 146S component concentration in a virus-containing suspension. The article presents a new approach to indirect determination of FMDV 146S component concentration in a non-inactivated suspension by comparing the maximum extreme points of the graphs of the second derivative of the fluorescence signal accumulation curves and the number of amplification reaction cycles. The dependence between FMDV 146S component concentration and the maximum extreme points of the graphs of the second derivative of the fluorescence signal accumulation curve is presented in the form of a square function: C146S FMDV = 0.0111(Cp)2 – 1.0157Cp + 20.446 with a high accuracy of approximation (R2 = 0.993). The proposed model allows to quantitatively estimate the content of 146S component in virus-containing vaccine raw materials. The presented method allows studying a large number of samples of non-inactivated raw materials for FMD vaccine in 4–5 hours. The main advantage of the proposed method is the capacity to determine the concentration of FMDV 146S component in a suspension with a high level of ballast proteins (more than 7.00 mg/cm3) and complete viral particles (from 0.01 to 5.00 μg/cm3).